Improvement of the Methodical Approaches to Evaluation of the Tourism Advertising Campaign Effectiveness - ROMANENKOV, Alexey Igorevich; KUTIN, Ilya Viktorovich; LEBEDEV, Kostyantyn Anatol'evich; GRZHEBINA, Liudmila Mihaylovna; SHIMANSKIY, Oskar Viktorovich (Journal of Environmental Management and Tourism, 2017)
It is established that methodical approach to full assessment of efficiency of advertising campaign can have three stages. The first stage includes assessment of advertising campaign efficiency through the analysis of advertising activity with account of additional factors. The second stage includes assessment of advertising campaign efficiency on the basis of particular, generalising and complex efficiency factors. The third stage implies full assessment of the process of advertising campaign efficiency management through the assessment of the company’s advertising position. A research has shown that general criterion of advertising campaign efficiency should be supplemented with a system of organizational and economic factors. Reliability of the presented methodical approaches to assessment of advertising campaign efficiency in tourism is confirmed by the introduction of the stage of nominal definition of advertising budget, in other words definition of usage directions of advertising efforts on the basis of singling out and justifying the necessity of certain types of advertising for a tourism company in a particular advertising cycle and creation of reserve fund for advertising campaigns.